Non-Linear Modeling and Control of Unmanned Air Vehicle - Ramezani, Roozbeh Falah (2012)
A Master of Science thesis in Mechatronics Engineering by Roozbeh Falah Ramezani entitled, "Non-Linear Modeling and Control of Unmanned Air Vehicle," submitted in May 2012. Thesis advisor is Dr. Ali Jhemi. Available are both soft and hard copies of the thesis.